Impact of iron deficiency on skeletal muscle function during physical activity - Téllez-Soleimán, Suad-Karime (2021)
Introduction: Vitamin and mineral deficiencies affect a third of the world’s population and explains about 7.3% of the global burden of the disease; among these deficiencies, iron deficiency affects approximately 2 billion people worldwide. There is evidence on the importance of iron for the performance of skeletal muscle, its deficiency being associated with decreased physical capacity and muscle fatigue. Materials and methods: A search of articles was carried out in databases such as PubMed and Google Scholar, using the MeSH terms "Physical work" "iron deficiency", "athletes", including clinical trials, in humans. Results: Out of a total of eight articles, three showed a significant difference in physical capacity in favor of those with higher levels of iron in serum tests, two articles did not show a significant difference between serum iron concentrations and physical capacity and four showed that the participants in the studies that carried out physical activity had a higher incidence of iron deficiency, thus suggesting that during physical activity there is a greater consumption and requirement of iron. Conclusion: There is a relationship between iron consumption and physical capacity, since those athletes with optimal iron levels have better physical performance and those with a higher physical demand are more prone to suffer from iron deficiencies.